Clinical study of PLA2R epitope spreading for predicting proteinuria remission in primary membranous nephropathy - Cheng, Xueyang; Zhou, Meiyi; Chen, Caimei; Xue, Jing; Liu, Bin; Zhang, Zhijian; Zhang, Xiran; Zhou, Leting; Cai, Ting; Huang, Biao; Zhang, Yi; Wang, Liang; et al. (Frontiers in Immunology, 2025)
IntroductionM-type phospholipase A2 receptor (PLA2R) is the predominant autoantigen in primary membranous nephropathy (PMN), accounting for approximately 70%–80% of cases. Circulating anti-PLA2R IgG is a widely used biomarker to monitor disease activity and treatment. In recent years, antibodies targeting specific PLA2R domains and epitope spreading of PLA2R have been identified and suggested to be correlated with disease severity and resistance to treatment. However, its clinical relevance remains controversial. This study aimed to evaluate whether epitope spreading offers superior prognostic value compared to total anti-PLA2R IgG levels in patients with PMN.MethodsThis retrospective study enrolled 74 patients with biopsy-proven PMN who underwent at least 6 months of follow-up. Clinical data and serum samples were collected at baseline (M0), 6 months (M6), and 12 months (M12). PLA2R-IgG, domain-specific antibodies (CysR-, CTLD1-, and CTLD7/8-IgG/IgG4), and anti-rituximab antibodies (ARAs) were measured using time-resolved fluorescence immunoassay. Logistic regression and receiver operating characteristic curve analyses were used to assess prognostic factors and model performance. The patients were divided into cyclophosphamide (CTX) and rituximab (RTX) treatment groups.ResultsThere were no significant differences in remission rates between the groups at M6 (CTX: 37.9% vs. RTX: 60.0%, P = 0.875) or M12 (61.5% vs. 75.6%, P = 0.220). However, the RTX group showed faster antibody clearance at M6 and a significantly higher immunological remission rate at M12 (96.2% vs. 65.6%, P = 0.017). In the RTX group, epitope spreading significantly decreased at M6 (P = 0.004), and four patients (22.2%) with no clinical remission were ARA-positive. Multivariate logistic regression analysis identified epitope spreading as an independent risk factor for non-remission at M6 (P = 0.031; AUC = 0.932). All four ARA-positive patients achieved partial or complete remission within 3–9 months after switching to obinutuzumab.DiscussionCompared with CTX, RTX induced a higher rate of immunologic remission at M12. Epitope spreading of PLA2R was identified as an independent risk factor for clinical remission after 6 months of treatment with RTX.